(untitled) (Comillas Journal of International Relations, 2019)
This paper focus on the bilateral relations between France and Spain during the 1986-2001 years, from the Spanish accession to the EEC to the beginning of the 2000 decade. Our working hypothesis is the birth during this period of a privileged relation between the two nations in the context of the European Community/European Union and in the post-Cold War era, represented by the relation between François Mitterrand and Felipe González. This work also highlights the limits of this partnership. The sources used are the French national archives (archives of the French presidency), diplomatic archives (France and Spain), archives of the EU and the press.